1993
DOI: 10.21273/hortsci.28.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Accumulation in Leaves and Cultured Cells during Heat Acclimation in Grapes

Abstract: Heat tolerance and endogenous ABA levels in leaves and cultured grape cells (Vitis spp., cultivars Venus and Veeblanc) were evaluated during beat acclimation. Plants and cultured cells were acclimated at 38 and 36C, respectively. Heat tolerance increased rapidly after exposing plants or cells to acclimation temperatures, reaching a maximum after 10 to 16 hours and 10 to 12 hours for leaves and cultured cells, respectively. Free and bound ABA levels increased sharply during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…For example, ABA concentration increased sharply in grape leaves during the first hour of heat stress (Abass and Rajashekar 1993). In our present study, shortterm heat stress treatment also quickly and significantly increased endogenous leaf ABA concentration in canola, relative to leaves of control plants held at the normal 20°C temperature (Fig.…”
Section: Resultssupporting
confidence: 69%
“…For example, ABA concentration increased sharply in grape leaves during the first hour of heat stress (Abass and Rajashekar 1993). In our present study, shortterm heat stress treatment also quickly and significantly increased endogenous leaf ABA concentration in canola, relative to leaves of control plants held at the normal 20°C temperature (Fig.…”
Section: Resultssupporting
confidence: 69%
“…It has been reported that exogenous ABA could alter thermotolerance of grape plants [5]. Our results showed that both heat and SA treatments increased ABA content (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Abass and Rajasheker [5] showed that both ABA content increased and heat tolerance enhanced to a maximum at the same time during heat treatment of grape leaves. Dat et al [6,7] reported that salicylic acid (SA) significantly accumulated in mustard seedlings during their exposure to heat, and thermotolerance of seedlings also increased.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term heat stress caused ABA increases in tobacco (Nicotiana tobacum) (Teplova et al 2000). Free and bound ABA concentrations increased sharply during the first hour of heat acclimation in grapes (Mahonia aquifolia) (Abass and Rajashekar 1993). In contrast, heat treatment does not cause ABA accumulation in tomato (Lycopersicon esculentum) (Bray 1991).…”
Section: Introductionmentioning
confidence: 98%
“…These include salicylic acid (Dat et al 1998a(Dat et al , 1998bLopez-Delgado et al 1998;Dat et al 2000;Larkindale and Knight 2002), active oxygen species (Larkindale and Knight, unpublished results), abscisic acid (Bonham-Smith et al 1988;Bray 1991;Abass and Rajashekar 1993;Robertson et al 1994;Larkindale and Knight 2002) and ethylene (Larkindale and Knight 2002). Arabidopsis mutant and transgenic plants unable to signal via SA, ABA and ethylene are all more sensitive to heat than wild-type plants, as are plants pre-treated with calcium or AOS signaling inhibitors (Larkindale and Knight 2002).…”
Section: Introductionmentioning
confidence: 99%